Factors associated with the use of long-acting contraceptive methods (LACMs): an analysis of Sleman HDSS 2016 - Dewi, Andham; Supriyati; Pangastuti, Heny Suseani (BKM Public Health and Community Medicine, 2021)
Purpose: This study aimed to analyze the relationship between individual and service-related factors and the use of long-acting contraceptive methods among women of reproductive age in Sleman Regency, Yogyakarta. Methods: This was a cross-sectional study using secondary data from the Sleman Health Demographic Surveillance System (HDSS) cycles 1 and 2. Study samples were married women of reproductive age who were using modern contraception. Multivariable analysis was performed using logistic regression. Results: The prevalence of LACM users in Sleman is 47.01%, while non-LACM users account for 52.99%. Variables included in the multivariable analysis were age, education, urban-rural status, socioeconomic status (SES), family planning services, type of care provider, and method of payment. Variables that significantly influence LACMs utility are urban-rural (OR=2.2; p=0.002; CI=1324-3,728), SES (OR=2.9; p=0,000; CI=1,768-5,041) free contraceptives (OR=17.22; p=0,000; CI=7.093-41.81), and national health insurance (OR=4.8; p=0,000; CI=2,923-7,930). Conclusion: Individual factors influencing the use of LACMs include place of residence and socioeconomic status, while health service factors include free contraceptive distribution and national health insurance.